Errors in Using English Verbs by EFL Students: Tenses and Aspects Analyses - Anita Purba; Arsen Nahum Pasaribu; Rotua Elfrida; Tiara K. Pasaribu (Scope : Journal of English Language Teaching, 2023)
Many scholars have conducted research on error analysis in English writing. However, scientific research on errors in using English verbs in terms of tense and aspect is still in its early stages. As a result, the purpose of this study was to identify the errors or mistakes in sentence translation from Indonesian to English that were related to tense and aspects. 25 English department students sat in the English syntax class and translated 12 Indonesian sentences into English. The findings reveal a total of 126 errors in sentence translation in terms of tense and aspect. The past perfect continuous tense, past perfect tense, present perfect continuous tense, future perfect continuous tense, future perfect tense, and future continuous tense are the most common errors. These findings indicate that the students were unfamiliar with the formulas and functions of these tenses, as well as aspect interpretation. As a result, English lecturers/teachers should prioritize English tenses and aspects for EFL students from the start.